Cobalt-Catalyzed Enantioselective Alkynylation of Oxabicyclic Alkenes - Wei, Lin-Wen; Ma, Zhan-Cai; Wang, Zhao-Qing; Zhao, Yu; Huang, Yuan (Synthesis, 2023)
Efficient access to enantioenriched cyclic homopropargylic alcohols through an unprecedented cobalt-catalyzed asymmetric alkynylation of oxabicyclic alkenes has been developed. By using inexpensive cobalt salt/chiral bisphosphine ligand as the catalyst and easy-to-handle potassium alkynyltrifluoroborates as the nucleophile, synthetically valuable homopropargylic alcohols are obtained in moderate to good yields and high enantioselectivities.
Keywords: cobalt catalysis; ring-opening; alkynylation; desymmetrization; oxabicyclic alkenes